Modelling Determinants of Return on Equity and Implications for Dividend Payout - I Kadek Bagiana; Kadek Indah Kusuma Dewi; Ni Luh Nyoman Sherina Devi; Luh Putri Mas Mirayani; Yura Karlinda Wiasa Putri (Universitas Batanghari Jambi, 2023)
The purposes of this study is to examine and get exact proof on the effect of CAR, NPL, OER, LDR on ROE and its implications for DPR. This study uses quantitative methods. Path analysis is utilized to demonstrate the connection between the factors considered. The results of the analysis show several findings including CAR has negative effect on ROE. NPL has no effect on ROE. OER has negative effect on ROE. LDR has negative effect on ROE. ROE has positive effect on the DPR. ROE mediates the effect of CAR on DPR. ROE is can’t to mediate the effect of the NPL on the DPR. ROE mediates the effect of OER on the DPR. ROE mediates the effect of the LDR on the DPR.